Application Of Fuzzy Logic Controllers In Temperature Regulation Of Gas-Fired Furnaces (The Peerian Journal, 2025)
This study evaluates the efficiency of applying Fuzzy Logic Controllers (FLC) for temperature regulation in gas-fired furnaces. The primary objective is to analyze the performance advantages of FLC compared to conventional PID controllers. A mathematical model and simulation of the fuzzy control system were developed to assess its effectiveness under varying operational conditions. Results demonstrate that FLC offers superior performance in terms of response time, stability, and reduced energy consumption. The findings underscore FLC's ability to enhance energy efficiency and maintain stable temperature control in industrial applications.